INTERNALISASI KARAKTER RELIGIUS DI SEKOLAH MENENGAH PERTAMA NURUL JADID - Muhammad Mushfi El Iq Bali; Nurul Fadilah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This research examines the internalization of religious characters in Nurul Jadid Junior High School. The purpose of this research is describe the internalization of religious characters in Nurul Jadid Junior High School, including understanding the definition of internalization and religious character, the method of developing the internalization of religious characters, knowing the strategy of internalizing religious characters in Nurul Jadid Junior High School, and SMP Nurul Jadid's efforts in internalizing religious characters. This is a qualitative research design using the fenomological approach. Strategy implementation of the internalization of religious characters in SMP Nurul Jadid can through two implementations, namely intrakurikuler and extracurricular activities based on “Panca Kesadaran and the Trilogy Santri” as a benchmark of character development that became the foundation of the main boarding schools of Nurul Jadid.